A Microgel Construction Kit for Bioorthogonal Encapsulation and pH‐Controlled Release of Living Cells1. Issue 51 (29th November 2013) - Steinhilber, Dirk; Rossow, Torsten; Wedepohl, Stefanie; Paulus, Florian; Seiffert, Sebastian; Haag, Rainer
Abstract pH‐Cleavable cell‐laden microgels with excellent long‐term viabilities were fabricated by combining bioorthogonal strain‐promoted azide–alkyne cycloaddition (SPAAC) and droplet‐based microfluidics. Poly(ethylene glycol)dicyclooctyne and dendritic poly(glycerol azide) served as bioinert hydrogel precursors. Azide conjugation was performed using different substituted acid‐labile benzacetal linkers that allowed precise control of the microgel degradation kinetics in the interesting pH range between 4.5 and 7.4. By this means, a pH‐controlled release of the encapsulated cells was achieved upon demand with no effect on cell viability and spreading. As a result, the microgel particles can be used for temporary cell encapsulation, allowing the cells to be studied and manipulated during the encapsulation and then be isolated and harvested by decomposition of the microgel scaffolds.